Webinar Sebagai Sumber Belajar di Tengah Pandemi COVID-19 - I Gede Dharman Gunawan; I Ketut Suda; Kadek Hengki Primayana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This paper discusses how webinar as a source of learning in distance learning. Now the Covid-19 pandemic has forced the learning system to change drastically from classroom learning to online learning. With the phenomenon of the many webinar activities carried out by educational institutions is a form of information technology utilization in the midst of Covid-19 pandemic. The benefits of participating in webinar include making themselves active in learning, increasing knowledge, and insight on current issues from various scientific disciplines. The advantages of attending a webinar is even free fees, share information quickly, and sometimes get a certificate.Keywords: Webinar; Learning Resources